Mechanical Rice Transplanting: A Labor-Saving Innovation Facing Adoption Challenges in Bangladesh - Ahmed, Sharif; Miajy, Abdullah; Bhandari, Humnath (International Rice Research Institute, 2025)
"In Bangladesh, 75% of the land is devoted to year-round rice production. Rice is typically grown using manually transplanted seedlings placed into puddled soil, although a small portion is also direct-seeded. Agricultural labor is declining sharply in Bangladesh, leading to high demand for workers during the peak transplanting period. Farmers typically do not have a wide window for transplanting due to various environmental factors and issues related to crop intensification. As a result of the high demand and labor shortages during this crucial time, labor prices often rise above normal levels. These increased transplanting costs significantly impact farmers' overall profit margins. Additionally, delaying the transplanting process can adversely affect crop yields. Mechanical rice transplanting holds significant importance for Bangladesh due to its potential to transform the country's rice production system (from conventional to mechanized). A rice transplanter is a mechanical device used to transplant rice seedlings from a tray or a nursery mat into a paddy field. Instead of manual planting (a very time-consuming and labor-intensive process), rice transplanter automates the task, ensuring even spacing and depth for optimal plant growth."